A Full-Time Nurse for Every School: A Call to Action to Make It Happen. (September 2017) - Nikpour, Jacqueline; Hassmiller, Susan
In June 2016, the American Academy of Pediatrics released its new policy statement recommending a full-time registered nurse in every school building. Indeed, increasing attention is being focused on school nursing, in part due to recent legislation, including the Affordable Care Act, the Healthy Hunger-Free Kids Act, and the Every Student Succeeds Act. Advocating for nursing practice within an education setting presents unique challenges in terms of changing the common perception of school nurses, variances in funding streams for school nursing, and the ability to link health outcomes with educational outcomes. The purpose of this article is to discuss the rationale for a school nurse in every building along with presenting action steps that individual and groups of school nurses can utilize to advocate for a full-time registered nurse in every school.